Superman, cultura visual e a configuração de nação nos Estados Unidos (1920-1950) - Raimundo, Roger Randerson Alves (2024)
This dissertation aims to analyze the power discourses linked to nation-building in the United States present in some of its visual and audiovisual productions during the years 1920 to 1950, mainly those linked to the defense of an urbanized and highly industrialized society; to gender performativities and the distinctions created between American citizens and those who were not considered fully citizens, especially the black and indigenous populations. Considering the methodologies used by other visual studies, we used the first series of animations of the character Superman (1941-1943) as the central axis of the research, and we mobilized an inventory of images composed of other image sources of the time, such as paintings, photographs, magazine advertisements and more animations produced by other major studios whose constructed and broadcasted discourses could be placed in dialogue with the superhero narratives throughout the analyses.